2012
DOI: 10.1002/polb.23127
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical heterogeneity of biodegradable poly(L‐lactide) homopolymer as revealed by temperature rising elution fractionation and successive self‐nucleation/annealing thermal fractionation

Abstract: Commercial poly(L‐lactide) is typically heterogeneous in chain structure due to the existence of a small amount of D‐lactyl units that are produced by the racemization reactions during the synthesis. In this article, the stereochemical heterogeneity of two commercial poly(L‐lactide) was investigated with temperature rising elution fractionation (TREF) and successive self‐nucleation/annealing (SSA) thermal fractionation. For both samples, three fractions were collected and characterized with rotatory power anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Figure 4a shows the survey DSC curves obtained from thermal fractionation experiments for pure POM and its blends with PLLA, and the representative SSA thermal fractionation curves are illustrated in Figure 4b–d. As observed in Figure 4a, the survey DSC curve of pure POM presents multiple melting behaviors corresponding to the number of SSA cycles, and each melting endothermic peak represents the melting of crystallites formed from the POM macromolecules with the similar oxymethylene sequence length and lamellar thickness [45], indicating that there is heterogeneity existing in POM resin [46]. Although the POM/PLLA blends exhibit the similar survey fractionation DSC curves with pure POM, it can also be identified that the SSA peaks in the blends mainly arise from the fraction crystallization of POM domain by comparing Figure 4b with Figure 4c,d.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4a shows the survey DSC curves obtained from thermal fractionation experiments for pure POM and its blends with PLLA, and the representative SSA thermal fractionation curves are illustrated in Figure 4b–d. As observed in Figure 4a, the survey DSC curve of pure POM presents multiple melting behaviors corresponding to the number of SSA cycles, and each melting endothermic peak represents the melting of crystallites formed from the POM macromolecules with the similar oxymethylene sequence length and lamellar thickness [45], indicating that there is heterogeneity existing in POM resin [46]. Although the POM/PLLA blends exhibit the similar survey fractionation DSC curves with pure POM, it can also be identified that the SSA peaks in the blends mainly arise from the fraction crystallization of POM domain by comparing Figure 4b with Figure 4c,d.…”
Section: Resultsmentioning
confidence: 99%